The Da Vinci code : a novel Dan Brown.. - Brown, Dan, 1964- (Anchor, 2006)
The secret Catholic organization known as Opus Dei has struck. The elderly curator of the Louvre has been found dead inside the museum, surrounded by eldritch ciphers in invisible ink. It is up to Harvard semiotician Robert Langdon and his French cryptologist partner Sophie Neveu to decode the cipers, and get to the bottom of an ever-widening mystery. They discover that the late curator was the gatekeeper of the "Priory of Sion", a secret society whose members included Leonardo da Vinci, and that he sacrificed his life to protect a vastly important ancient religious relic from Opus Dei. If Langdon and Neveu do not deciper the clues in time, Opus Dei will get its hands on the relic, and havoc will be wrought.